- Difference of two squares
- a2- b2 = (a + b)(a - b)
- x2- 25 = (x + 5)(x - 5), x2- 36= (x + 6)(x - 6) ,x2- 49 = (x + 7)(x - 7)
- a2- b2 = (a + b)(a - b)
- Trinomial perfect squares
- a2 + 2ab + b2 = (a + b)(a + b) or (a + b)2
- x2 + 14x + 49 = (x + 7)2, x2 + 10x + 25 = (x + 5)2, x2 + 12x + 36 = (x + 6)2
- a2 - 2ab + b2 = (a - b)(a - b) or (a - b)2
- x2 + 14x + 49 = (x + 7)2, x2 + 10x + 25 = (x + 5)2, x2 + 12x + 36 = (x + 6) fference of two cubes
- a3 - b3
- 3 - cube root 'em
- 2 - square 'em
- 1 - multiply and change
- 3 examples
- a3 - b3
- Sum of two cubes
- a3 + b3
- 3 - cube root 'em
- 2 - square 'em
- 1 - multiply and change
- 3 examples
- a3 + b3
- Binomial expansion
- (a + b)3 = Use the pattern
- (a + b)4 = Use the pattern
thoughts on math- Jeremy Troup
Wednesday, November 17, 2010
Wednesday, October 13, 2010
Subscribe to:
Posts (Atom)